UPAYA MENINGKATKAN PERAN PERPUSTAKAAN SMP BATIK PROGRAM KHUSUS SURAKARTA SEBAGAI PERPUSTAKAAN YANG PROFESIONAL - Yessy Primadani Tungga Dewi; Zainal Arifin (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
The purpose of this study was to determine the efforts to increase the role of the Surakarta Special Program Batik Middle School library as a professional library. The study used a qualitative descriptive method. The research subjects were teachers and librarians at the Surakarta Special Program Batik Junior High School. The time of the research was carried out during the Internship of the Library Management Practice starting on March 19-March 26, 2021. The data sources came from interviews, observations, and direct documentation at the Surakarta Special Program Batik Middle School. The data of this research are matters related to efforts to increase the role of the school library as a professional library. Data collection techniques in the form of interviews, observations, and documentation. The data analysis technique used is data reduction. The results of this study are efforts that can improve the Surakarta Special Program Batik Middle School library as a professional library including: 1) complementing library materials or collections in the library, 2) providing maximum library services in the form of borrowing and returning books, hotspot services that can accessible to anyone, and reference services, 3) providing adequate library facilities and infrastructure, 4) library management is carried out by teachers who also serve as librarians and are given training or workshops related to library science, and 5) organize library rooms according to standards.